Probabilistic design of a newly designed cemented hip prosthesis using finite element method - EKİCİ, BÜLENT (ELSEVIER SCI LTD, 2008)
The finite element method is an important tool used in the design of orthopedic prosthesis. One of the important orthopedic applications is hip prosthesis replacement. This operation is so complex that it requires close co-operation between engineers and surgeons. They have to work together in order to produce durable and reliable hip joint prosthesis. The reason for this is that the nature of bone strongly affects the design. In reality, uncertainties exist in the system and environment that may make the application of a deterministic design decision unreliable. That is, the values of the variables that are acting on the system cannot be predicted with certainty. For instance, probabilistic approach was applied to the model after deterministic design results. Thus, using probabilistic approach reliability of newly design cemented hip prosthesis was quantified. The new design is modeled parametrically to investigate the effects of different geometrical parameters on the relative displacement. These parameters are then optimized. Using the results of this investigation, the probability of failure was investigated for both the initial and shape-optimized prosthesis designs using several simple performance functions describing fatigue theory (Goodman, Gerber, Soderberg), static and dynamic failure of the cement-pros thesis interface. The optimum geometry and material properties are then compared with Charnley's implant results. 0 2007 Elsevier Ltd. All rights reserved.
Keywords: probabilistic design; reliability; fatigue; finite element method; hip prosthesis; SHAPE OPTIMIZATION; STEM